Chromatin CKAP2, a New Proliferation Marker, as Independent Prognostic Indicator in Breast Cancer - Kim, Han-Seong (Public Library of Science, 2014)
BACKGROUND: The level of proliferation activity is a strong prognostic or predictive indicator in breast cancer, but its optimal measurement is still in debate, necessitating new proliferation markers. In the present study, the prognostic significance of the CKAP2-positive cell count (CPCC), a new proliferation marker, was evaluated, and the results were compared with those for the mitotic activity index (MAI). METHODS: This study included 375 early-stage breast cancer samples collected from two institutions between 2000 and 2006. Immunohistochemical staining was performed using a CKAP2 monoclonal antibody. Cox proportional hazard regression models were fitted to determine the association between the CPCC and relapse-free survival (RFS) amongst three groups formed on the basis of the CPCC or MAI value: groups 2 and 3 showing the middle and highest values, respectively, and group 1 the lowest. RESULTS: After adjustment for age, T stage, N stage, HER2 status, estrogen receptor status, progesterone receptor status, institution, and year of surgical resection, the CPCC was associated with a significantly worse RFS {hazard ratio [HR]  = 4.10 (95% CI: 1.64–10.29) for group 2; HR  = 4.35 (95% CI: 2.04–10.35) for group 3}. Moreover, its prognostic significance was similar to or higher than that based on the MAI {HR  = 2.05 (95% CI: 0.94–4.65) for group 2; HR  = 2.35 (95% CI: 1.09–5.10) for group 3}. In subgroup analyses, the CPCC showed a prognostic significance in the luminal A and triple-negative subgroups, but not in the HER2-positive subgroup. CONCLUSIONS: Chromatin CKAP2 is an independent prognostic marker for RFS in early-stage breast cancer, and could potentially replace the MAI in clinical evaluation of proliferation activity. Additionally, our study results suggest that the prognostic significance of proliferation activity differs among the various subgroups of breast cancer.